SAT0132 The rheumatoid arthritis flare questionnaire (RA-FQ): results of rasch analysis and feedback on real-world applications from international RA patients and clinicians. (15th June 2017) - Bartlett, SJ; Barbic, SP; Bykerk, VP; Fautrel, B; Guillemin, F; Broeder, A den; Alten, R; Christensen, R; Choy, E; Furst, D; Hewlett, S; Leong, A; et al.
Abstract : Background: Disease flares in RA are common. The RA Flare Questionnaire (RA-FQ) can be used to identify and quantify flares in rheumatoid arthritis (RA). Objectives: To further explore the psychometric properties RA-FQ, we used Rasch analysis and reviewed results with RA patients research partners (PRPs) and clinicians to gain additional insight into the interpretability, meaningfulness, and utility of results. Methods: People with RA in observational trials in Canada (CATCH; n=896) and France (STPR; n=138), and an RCT in the Netherlands (n=178) completed the RA-FQ. RUMM2030 was used to evaluate unidimensionality, targeting of items to people, reliability, response options, redundancy, local dependence, and response bias by sex, across age categories, and by country/language. ROC curves were used to identify sensitivity and specificity across potential threshold values to identify flares in different contexts of use. We reviewed results with RA patients research partners (PRPs) to gain additional insight into the interpretability, meaningfulness, and utility of results. Ten PRPs first completed the questionnaire then reviewed individual and group findings to provide feedback. RA clinicians provided feedback on utility and relevance of proposed cut points to identify flares. Results: Rasch results supported the simple summation of items for a total score ranging from 0–50. Each item had ordered thresholds and acceptable fit. Reliability, was high (PSI =.91). Items and people covered a continuum ranging from -3.2 to +3.4 logits, and items were well-targeted to respondents. Overall model fit was excellent (χ 2 =31.6, df=45; p=0.935). There was little evidence of differential item functioning by sex, age, or country/language. Items suggest flare symptoms and impacts increased together showing a consistent story of how individuals experience worsening RA disease activity. Among PRPs, scores ranged from 10 to 41. There was unanimous agreement from the patients that the story depicted and individual results obtained were easily understood, meaningful, and very reflective of their current state. Many patients noted that beyond clinical trials, the RA-FQ could also enhance communication between doctors and patients at routine visits. Several noted potential applicability in monitoring day-to-day status and with self management. Thresholds for clinically important worsening to identify flare varied by setting, patient population, and context of use. Conclusions: Taken together, results from classical and Rasch analyses support for the robust psychometric properties of the RA-FQ. The 5-item measure is easy to complete and simple to score. Feedback from RA PRPs and clinicians increase confidence in the relevance, meaningfulness, and easy interpretation of RA-FQ results for clinicians, researchers, and patients. Disclosure of Interest: None declared